The Validity and Reliability Test of Modified Picture Vocabulary Test IV in 48-59 Months Old Children - Sumarni; Amendi Nasution; Luh K Wahyuni; Trevino Pakasi (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objectives: To investigate the validity and reliability of Modified Picture Vocabulary Test IV (PPVTIV) in 48-59 months old child. Methods 228 items in 19 sets of PPVT IV were translated in Indonesian language and revised according to Indonesian culture. One hundred and five 48-59 months old children were tested. The results wereanalyzed for its construct validity and reliability. The construct validity was valued by the correlation coefficient between the set score and the total score and the correlation coefficient between the itemscore and the set score. The reliability was valued by intra-class correlation coefficient, standard error of measurement (SEM) and Cronbach alpha.Results: The construct validity of Modified PPVT IV was good (r>0.256; α=0.01 n=100) and the reliability was high (internal consistency with Cronbach alpha= 0.938, inter-rater reliability= 0.957-0,985 and standard error of measurement (SEM) = 6.4).Conclusions: Modified PPVT IV was a valid instrument with satisfactory reliability. To increase the construct validity, there were 36 items that should be substituted.Key Words: Modified PPVT IV, construct validity, internal consistency reliability, inter-rater reliability, standard error of measurement Received in